Effects of planting date, cultivar and insecticide spray application for the management of insect pests of cowpea in northern Ghana. (October 2017) - Abudulai, Mumuni; Kusi, Francis; Seini, Shaibu S.; Seidu, Ahmed; Nboyine, Jerry A.; Larbi, Asamoah
Abstract: Insect pests are a major constraint to cowpea production in northern Ghana where it is widely cultivated. Field experiments were conducted to evaluate the effects of planting date, cultivar and insecticide applications for the management of major insect pests attacking cowpea. There were 4 planting dates, 6 cowpea cultivars of medium maturity periods and 2 insecticide spraying regimes. Data were collected on densities of the major insect pests, including the legume pod borer Maruca vitrata F., thrips Megalurothrips sjostedti Trybom, and the pod-sucking bug complex dominated by Clavigalla tomentosicollis Stal., and grain yield. Early planting of cowpea in mid- or late July resulted in the lowest pest densities compared with those planted at later dates. Two of the six cowpea varieties (IT99-573-2-1 and IT99-573-1-1) supported the lowest numbers of insects across planting dates and irrespective of insecticide spraying regime. However, insecticide sprays significantly lowered pest densities and improved yields in all varieties, and yields were the highest when treatments were combined with early planting in mid-July. The results suggest that for maximum yield, cowpea in the study area should be planted in mid-to-late July and sprayed with insecticide. Where available, these treatments can also be integrated with varieties such as IT99K-573-2-1 and IT99k-573-1-1 which appeared to be less susceptible to insects in the current study. Highlights: Insect pests limit cowpea yields in northern Ghana. Planting early in mid or late July results in less insect attack and is recommended. This planting time also gives plants a longer season for growth and development. Pesticide protection is recommended when planting is delayed or late. Integrating these controls with less susceptible varieties is recommended.